Controle de qualidade de cosméticos capilares para coloração oxidativa permanente: uma breve descrição - Corrêa, Rita de Cássia Oliveira (Universidade Federal de São Carlos, 2022)
Brazil as a country among the 4 largest consumers of cosmetic products in the world, and the growth of this sector generates the need for improvement and development of cosmetics, among which the capillaries and for this, it is necessary to know the product through technical analysis. This work aims to expose and understand the main analytical methods aimed at oxidative hair coloring that will be able to characterize and qualify the product, both for the final consumer and for its knowledge and improvement. Among the analyses, we have the organoleptic ones, which include the appearance, odor and color tests, which aim to observe the behavior of the sample making use of the human senses, they are essential because these factors are the ones mainly observed by the color users, so they dictate the product functionality. In addition to these, we have the physical-chemical tests which are able to provide technical data on the sample, such as pH, viscosity, density, among others, which are important for regulation and quality control of the cosmetic. Therefore, there is a need for analytical tests that allow greater technical knowledge about the product, taking into account that hair is a complex matrix and it is necessary to have a foundation about the compositions that will be applied on it.
Quality control of hair cosmetics for permanent oxidative coloring: a brief description
Keywords: Cosméticos capilares; Análises; Estrutura capilar; Hair cosmetics; Analyses; Hair structure; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA